(NsPEKTRALXNYE SWOJSTWA OB_EMNYH INTERFERENCIONNYH WOLN W LITOSFERE (B/s - (NhARITONOW(B, (NoLEG mATWEEWI^s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 225-240 (357 (NNAZW(B.)s
(Nan ussr(B, (NiN(B-(NT GEOFIZIKI IM(B. (Ns(B. (Ni(B. (NsUBBOTINAs
Keywords: (NsEJSMI^ESKAQ RAZWEDKAs; (NsEJSMI^ESKIE WOLNYs